Analisis Faktor-Faktor yang Mempengaruhi Partisipasi Angkatan Kerja Wanita di Berbagai Konteks Sosial dan Geografis di Indonesia - Iffah, Nisa Al; Bachtiar, Nasri (SAFE-Network, 2024)
In 2021, the male labor force participation rate in Indonesia will reach 85.21%, while female participation is only 62.63%, showing a gap of 22.58%. This research describes the factors that influence female labor force participation in Indonesia using human capital theory, labor supply theory, and labor Leisure Choice theory. Using the logit method and Sakernas data for August 2021 (sample 393,359 people), it was found that education level, certified training, marital status, ownership of health insurance, and work experience had a significant effect on female labor force participation. Education and training levels weaken positively with increasing work participation. Marital status and possession of health insurance also made positive contributions, indicating the role of social support and financial security. However, the number of working hours and regional classification of residence negatively influenced participation, limiting the challenges of women with high workloads or living in areas with limited economic accessibility. These findings underscore the complexity of factors influencing women's labor force participation in various social and geographic contexts in Indonesia.